A Focused Review of the Metabolic Side-Effects of Clozapine - Yuen, Jessica W. Y.; Kim, David D.; Procyshyn, Ric M.; Panenka, William J.; Honer, William G.; Barr, Alasdair M. (Frontiers in Endocrinology, 2021)
The second generation antipsychotic drug clozapine represents the most effective pharmacotherapy for treatment-resistant psychosis. It is also associated with low rates of extrapyramidal symptoms and hyperprolactinemia compared to other antipsychotic drugs. However, clozapine tends to be underutilized in clinical practice due to a number of disabling and serious side-effects. These are characterized by a constellation of metabolic side-effects which include dysregulation of glucose, insulin, plasma lipids and body fat. Many patients treated with clozapine go on to develop metabolic syndrome at a higher rate than the general population, which predisposes them for Type 2 diabetes mellitus and cardiovascular disease. Treatments for the metabolic side-effects of clozapine vary in their efficacy. There is also a lack of knowledge about the underlying physiology of how clozapine exerts its metabolic effects in humans. In the current review, we focus on key studies which describe how clozapine affects each of the main symptoms of the metabolic syndrome, and cover some of the treatment options. The clinical data are then discussed in the context of preclinical studies that have been conducted to identify the key biological substrates involved, in order to provide a better integrated overview. Suggestions are provided about key areas for future research to better understand how clozapine causes metabolic dysregulation.